Predictive factors for failure of salpingostomy in ectopic pregnancy. Issue 2 (10th October 2013) - Kayatas, Semra; Demirci, Oya; Kumru, Pinar; Mahmutoglu, Didar; Saribrahim, Bahar; Arinkan, Sevcan Arzu
Abstract Aim The objective of this study was to review our experience with ectopic pregnancy management and to evaluate major predictive factors for failure of conservative linear salpingostomy. Methods Seven hundred and ninety‐seven cases that were treated for ectopic pregnancy in our clinic between October 2005 and September 2011 were analyzed retrospectively for incidence and treatment options. We defined failure as rising or plateauing postoperative serum β‐hCG levels that required additional medical or surgical treatment after initial removal of the ectopic pregnancy by laparoscopy or by laparotomy. We examined the risk factors consisting of preoperative β‐hCG, size and location of ectopic lesions, the presence of fetal heart beat and tubal condition that can influence the failure or success of conservative salpingostomy. Results In total, 403 patients were treated conservatively. These conservative managements consist of 334 salpingostomies performed by laparoscopy and 69 by laparotomy. Because of persistent ectopic pregnancy, 16 patients underwent medical treatment. In total, 387 patients were treated successfully with conservative management and 16 patients were treated unsuccessfully with conservative management. When variables of P < 0.05 were subjected to multivariate analysis, size of the ectopic pregnancy of 33.5 mm or greater and fimbrial and isthmic region ectopic pregnancies were significantly associated with the failure rate. Conclusions The size of the ectopic pregnancy and fimbrial and isthmic region ectopic pregnancies were determinant of failure of conservative surgery. Our success rate in the ruptured group is not an underestimated value to dissuade patients wishing to maintain fertility by undergoing salpingectomy. So, the conservative approach to ectopic pregnancy should be undertaken after careful patient evaluation.